Crystal growth and characterization of thulium calcium oxyborate high-temperature piezoelectric crystals. Issue 3 (24th October 2014) - Hou, Shuai; Yu, Fapeng; Liu, Yanqing; Zhang, Shujun; Lu, Qingming; Wang, Shenglai; Zhao, Xian
Abstract : High-temperature stability of electromechanical and piezoelectric properties was obtained for TmCa4 O(BO3 )3 crystals over the temperature range of 20–900 °C. Abstract : New rare-earth calcium oxyborate crystals TmCa4 O(BO3 )3 (TmCOB) were grown by using the Czochralski pulling method, and the mechanical and thermal properties were investigated. In addition, the dielectric, elastic and piezoelectric performance was evaluated by impedance measurement, where the piezoelectric charge coefficients were determined to be on the order of d 11 = 1.7, d 12 = 3.8, d 13 = −4.2, d 15 = −0.92, d 24 = 4.9, d 26 = 7.8, d 31 = −0.75, d 32 = −2.4, d 33 = 2.2 and d 35 = −5.2 pC N −1 . The temperature-dependent electrical resistivity and electro-elastic properties were studied from room temperature to 900 °C, where a high electrical resistivity of 6 × 10 7 Ω cm and a low dielectric loss of 21% were achieved at 900 °C, with high thermal stability of electromechanical coupling factors and piezoelectric coefficients over the temperature range of 20–900 °C. All of these properties demonstrate that TmCOB crystals are an attractive candidate for high-temperature sensor fabrications.